The integration of Spanish and Portuguese organ music within the liturgy from the latter half of the sixteenth to the eighteenth century - Nelson, B (1987)
Spanish and Portuguese organ music still remains a relatively unchartered area escaping the attention of most general assessments of European musical history. The work which has been done in this field has tended towards stylistic appreciations of the published large-scale compositions and the compilation of short biographies of prominent musicians. No extensive investigation has yet been undertaken which deals with such fundamental issues as the role of the organist and the origins and function of the extant organ repertory, of which a large proportion lies dormant in manuscripts, within the liturgy. Indeed, there is no monograph about organists and organ music in the Iberian peninsula as a whole. The overall aim of this thesis is to provide a musical background and liturgical context for short organ pieces called versos which were thoroughly integrated within a musical celebration of the Offices. For this end, a variety of musical and documentary material has been examined: practical sources of organ music; plainchant manuals; ceremonials and musical treatises. To an enormous extent this organ music was subject to long-standing liturgical customs and legislation, as well as to strongly defined traditions of musical composition. The prescriptions to the organist given in the ecclesiastical constitutions and how these may have been realized in the Canonical Hours and in the Mass constitutes the essence of part two of this thesis. This interpretation of musico-liturgical practices has entailed an examination of the relationship between plainchant and the organ verset and the technicalities of mode and tranposition which were involved when alternating the organ with choral plainchant. An analysis is also made of the musical development of versets based on the psalm-tones, organ hymns (the Pange lingua in particular) and the 'organ mass'. An anthology of transcriptions complementing this discussion is contained in a separate volume. As a counterbalance to the analytical discussion in part two, part one provides an historical and cultural background to the subject. An assessment is made of the contribution made by individual organists and organ 'schools' and some consideration is made of the extent to which both royal and ecclesiastical patronage was responsible for the livelihood of music and the arts.